Assessment of medical and economic consequences of diabetes type 1 and 2 in Poland - Kawalec, Paweł (2007)
The objective of a dissertation was an assessment of direct and indirect costs referring to diabetes type 1 and 2 in population of Cracow in 2004; economic burden of the disease has been assessed and influence of direct and indirect medical costs on total diabetes burden in Poland has been defined. To assess the burden of diabetes in population of Cracow direct medical costs of diagnosis and treatment were calculated based on medical resources consumption reported in Department of Endocrinology of Jagiellonian University Collegium Medicum and Chart of Internal Medicine of Railway Regional Hospital in Cracow in years: 2001-2003. A special questionnaire was used to assess medical resources consumption due to diabetes treatment mainly based on data on insulin and oral hypoglycemic drugs consumption during hospitalization and 12 months afterwards. Retrospective data was collected about therapy regimes in case of 381 patients treated in the above mentioned clinical centers. An annual costs of hospitalizations and ambulatory treatment of standard patient were taken into account; standard medium cost of in-patient therapy as well as number of re-hospitalizations in 12 months period and a number of ambulatory visits in case of out-patient treatment was calculated based on registers in both medical centers. Average annual costs of a standard patient treatment with diabetes type 1 were:
Keywords: indirect costs; direct medical cost and direct non-medical costs; diabetes; burden of disease